Fifty years of the pericardial valve: Long‐term results in the aortic position. Issue 8 (12th May 2021) - Balmforth, Damian; Dimagli, Arnaldo; Benedetto, Umberto; Uppal, Rakesh
Abstract: It is now 50 years since the development of the first pericardial valve in 1971. In this time significant progress has been made in refining valve design aimed at improving the longevity of the prostheses. This article reviews the current literature regarding the longevity of pericardial heart valves in the aortic position. Side by side comparisons of freedom from structural valve degeneration are made for the valves most commonly used in clinical practice today, including stented, stentless, and sutureless valves. Strategies to reduce structural valve degeneration are also discussed including methods of tissue fixation and anti‐calcification, ways to minimise mechanical stress on the valve, and the role of patient prosthesis mismatch.